(untitled) (Journal of the College of Education for Women, 2019)
The research aims to learn spatial disparities tracts of agricultural crops in theprovince of Maysan and their relationship (the salinity of the soil and the degree of chemicalinteraction (PH)) The research is divided into an introduction and three Investigation eat firstsection spatial disparities agricultural crops (cereals, vegetables, legumes and forage). Thecomparison between the years of production in the province where the province has seenvaried spatial by hand and taking second section degrees of soil salinity and its impact onagriculture, as well as the chemical reaction (PH) and its impact on agriculture The thirdsection has been used three technical techniques first linkage and the second simple and thirdresiduals regression relative for multiple regression and Arafa The relationship between soilproperties and land use have ranged relationship between the medium and strong as well asthe presence of a weak relationship.The research came out with recommendations include the need to reduce theincreasing salinization of the soil and rely on modern methods of irrigation. Alodhafah Alqlahto educate and raise the efficiency and improve the infrastructure and the environmentAlstunaih for rural residents and raise the yield per dunam